Subarachnoid hemorrhage – Induced block of cerebrospinal fluid flow: Role of brain coagulation factor III (tissue factor). Issue 5 (May 2018) - Golanov, Eugene V; Bovshik, Evgeniy I; Wong, Kelvin K; Pautler, Robia G; Foster, Chase H; Federley, Richard G; Zhang, Jonathan Y; Mancuso, James; Wong, Stephen TC; Britz, Gavin W
Subarachnoid hemorrhage (SAH) in 95% of cases results in long-term disabilities due to brain damage, pathogenesis of which remains uncertain. Hindrance of cerebrospinal fluid (CSF) circulation along glymphatic pathways is a possible mechanism interrupting drainage of damaging substances from subarachnoid space and parenchyma. We explored changes in CSF circulation at different time following SAH and possible role of brain tissue factor (TF). Fluorescent solute and fluorescent microspheres injected into cisterna magna were used to track CSF flow in mice. SAH induced by perforation of circle of Willis interrupted CSF flow for up to 30 days. Block of CSF flow did not correlate with the size of hemorrhage. Following SAH, fibrin deposits were observed on the brain surface including areas without visible blood. Block of astroglia-associated TF by intracerebroventricular administration of specific antibodies increased size of hemorrhage, decreased fibrin deposition and facilitated spread of fluorophores in sham/naïve animals. We conclude that brain TF plays an important role in localization of hemorrhage and also regulates CSF flow under normal conditions. Targeting of the TF system will allow developing of new therapeutic approaches to the treatment of SAH and pathologies related to CSF flow such as hydrocephalus.